Interelation of Public Relations Management to Enhance Community Participation in School - Ismail, Ahmad Nur; Priyono, Ali; Roziqin, Muhamad Khoirur; Tamwifi, Irfan (Khatulistiwa, 2021)
The purpose of this study was to describe the interrelationship of public relations management in increasing community participation in Islamic elementary school. An ethnographic study was used, with a comprehensive qualitative descriptive analysis. The results of this study; The planning of the work program in the field of public relations at Islamic elementary school has been carried out well, through a mechanism that is carried out at the beginning of each school year led directly by the principal. The principal conducts periodic evaluations of the Public Relations program, and it is carried out effectively and efficiently. Community participation is quite good and enthusiastic, by implementing a strategy of providing examples, maximum service, working sincerely, and establishing friendship.